The mentalist. The complete sixth season [videorecording (DVD)] - Baker, Simon, 1969-; Baker, Simon, 1969-; Tunney, Robin; Kang, Tim, 1973- (Warner Bros. Entertainment, 2014)
Armed with a list of seven suspects confirmed by the killer himself, Patrick Jane and the CBI team are closing in on the elusive serial killer while continuing to solve California's most puzzling crimes. Could Red John be a cult leader? A ghoulish forensic analyst? A super-suspicious Homeland Security Agent? Or one of four law officials, including the director of the CBI himself? The identity of the man who killed Patrick Jane's family is finally revealed in a climactic showdown.